Processo de apropriação da escrita alfabética no 3º ano do ensino fundamental e as contribuições do programa de escrita inventada - Josiane de Assunção Marcelos (2024)
This intervention research addresses the challenges of literacy highlighted in the context of the Covid-19 pandemic, discussing the relationship between the interruption of faceto- face classes and the process of appropriation of alphabetic writing by children in the 3rd year of Elementary School who have graduated from remote education. The investigation sought to answer which pedagogical mediation strategies could guarantee the appropriation of writing words composed of complex syllables for children in the 3rd year of Elementary School, post-pandemic. The research was carried out in a state public school in the city of Belo Horizonte, with 19 participating children and organized into 5 heterogeneous groups in relation to knowledge about the writing system. This intervention research is based on the methodology of the Invented Writing Program and is based on phonological, interactionist and sociointeractionist concepts. The first methodological procedure consisted of an initial writing diagnosis interpreted based on the writing levels defined by Emilia Ferreiro from the main research to the most recent studies. 8 writing sessions of the Program were carried out and a final diagnosis was carried out to analyze the writing data, obtained by contrasting the productions carried out in the proposed tasks. The study highlights the influence of intrasyllabic elements and the relevance of adult mediation in the process of appropriation of writing complex syllables by children, when provoked to graphophonemic reflection, adopting the following mediation strategies: group management, word contextualization, phonological clues , written record, verification reading, comparison between invented writing and conventional writing. The main results indicate progress in alphabetic writing, with an increase in the number of pertinent relationships between graphemes and phonemes that make up the complex syllable and allow us to defend that the Invented Writing Program, by proposing collaborative learning situations to the detriment of syllable memorization strategies and Copying words enhances the appropriation of alphabetic writing by children. Based on the study carried out, a Research Glossary in e-book format was created as an educational product, presenting 23 concepts, terms and questions on the appropriation of alphabetic writing, communicating the results of intervention research.